Developing The Model of Integrated Social Safety Net Programmes Towards Better Financial Well-Being - Din, Badariah; Habibullah, Muzafar Shah; Abdullah, Hussin; Safuan, Sugiharso; Osman, Azim Azuan (Russian Law Journal, 2023)
Social safety net initiative is essentially a set of policies and programmes designed to ensure basic standards of living in a nation are met and protecting people from economic shocks. Despite various social safety net programmes have been delivered by the government to serve these objectives, studies that propose alliance between provision of public assistance, corporate social responsibility programmes and beneficiaries’ self-coping mechanism are very scarce. Therefore, this study aimed to conceptualise a model that integrate the role of public assistance, corporate social responsibility and self-coping mechanism towards better financial well-being of low-income earners in Malaysia. This model attempted to explain the relationship between social safety net programmes delivered by the government and private companies on beneficiaries’ financial well-being. Besides social safety net programmes, financial behaviours of the beneficiaries were also hypothesised as the intervening variable between social safety net programmes and financial well-being. The model produced in the present study deemed to offer a good direction for socio-economic scholars and policy makers in improving Malaysians’ financial well-being through better governance and delivery of social safety net programmes in the future.